Belarus Scaling Up Energy Efficiency Retrofit of Residential and Public Buildings : Assessment of Investment Needs, Implementation Constraints, Financing Options, and Delivery Models - World Bank Group (World Bank, Washington, DC, 2016)
The Republic of Belarus relies heavily on natural gas imports to meet domestic energy demand. Energy efficiency (EE) investments can significantly reduce budget outlays in the long-term while also improving the physical assets and quality of energy services. Investments in thermal retrofits of public and residential buildings can result in substantial economic benefits. Recognizing the substantial energy savings potential in the buildings sector, the Government of the Republic of Belarus (GoB) has introduced policies and programs to promote the development of more energy efficient buildings, and the retrofitting of old buildings. The integrated program for design, construction, and renovation of energy-efficient housing in the Republic of Belarus for 2009-2010 and until 2020 sets a national target to reduce specific heat consumption in existing residential buildings by 60 kWh per